(untitled) (International Journal of Current Engineering and Technology, 2014)
This paper envisages an experimental investigation on turning of AISI 8620 alloy steel using PVD coated cemented carbide CNMG inset. Nine experimental runs based on Taguchi factorial design were performed to find out optimal factio level condition. The main focus of present experimentation is to optimize the process parameters namely spindle speed, feed and depth of cut for desired response characteristics i.e. surface roughness, VMRR and interface temperature. To study the performance characteristics in this work orthogonal array(OA), analysis of means(ANOM) and analysis of variance(ANOVA) were employed.The experimental results showed that the spindle speed affects more on surface roughness, feed affects more on VMRR and feed affects more on interface temperature.Confirmation tests also been performed to predict and verifythe adequacy of models for determining optimal values of response characteristics.